Studi Metode Dakwah Ceramah Persuasif yang digunakan Ustad Jamil di Masjid At-Tauhid Betiting Surabaya pada Pengajian kitab Al-Wajiz fi Fiqh Sunnah (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2020)
researchthe study method comunications persuasive, use teacher Jamil in the moscue at-Tauhid Betiting Surabaya at study book al-Wajiz fi fiqh Sunnah. I interest with the research because teacher jamil use method can interest many people in the place around. After I study thing it real at the place it. Many people come at recitation fiqh book it, becausemany people interest with method teacher jamil. Teacher Jamil use method persuasive communication, and withuse  style attractive of communications, in order that increase many people very happy. In the research it. I Research connection between communication persuasive and theory persuasive and then I find result very well, able appropriate between both. I find so method Teacher Jamil  appropriate how to communication Islam in the Al-Qur’an and Sunnah Rasulullah Shalallahu alaihi wasallam. And detail teacher Jamil use method asosiasi, and method pay-off  and fear-arousing, sometimes teacher Jamil connection messages persuassive. With social reality factual in order that message it. Can accept because of social. In order that sum society come to recitation fiqh book can increasingly sum people. And social can understanding message religion from teacher Jamil. For instance it very well for progress build moeslem social in the around place it.